First Record of Quill Mites (Acariformes: Syringophilidae: Picobiinae) Living in the Quill Walls of Parrots. Issue 6 (17th June 2019) - Skoracki, Maciej; Sikora, Bozena; Hromada, Martin
Abstract: Quill mites (Acariformes: Prostigmata: Syringophilidae) are a family of about 400 ectoparasite species known to infest birds for over 140 yr. All previously identified quill mites occur in the calamus, a cavity of the bird feather, where they spent their entire life except for a short dispersion period. In this study, we report the first record of quill mites dwelling in the quill walls during their entire life cycle. In short, we found all of the different life stages of the species Lawrencipicobia poicephali (Skoracki & Dabert 2002) (Acariformes: Syringophilidae) in the quill wall in 33 host individuals of six different host species from many different locations in Sub-Saharan Africa. Hosts were collected over a time period spanning more than 70 yr. Lastly, we report six new avian hosts for this ectoparasite species.